Creating Your Perfect Family Size : How to Make an Informed Decision About Having a Baby - Singer, Alan M., 1955- (San Francisco Jossey-Bass, 2011)
"Answers to one of the most important decision a family can make. This groundbreaking book offers answers to crucial questions that have a large impact on family success and well-being. The author has been researching and treating couples for more than twenty years, addressing such critical issues as: When should you have kids? How many and why? Can you afford a family? What's the best interval between children's birth in a family? How does your work life influence how many kids to have? What's the impact of divorce, remarriage and blended families on the decision to have more kids? How does your family of origin, ethnicity, race, culture, and sexual preference influence the choices you have regarding these questions of number and spacing of childbirths. Filled with common sense advice for the dilemmas most couples grapple with when starting a family. Based on solid research from a noted family therapist. Alan Singer has appeared on the Fox Morning News and MSNBC as well as being quoted in USA Today and The Huffington Post. Invaluable and fascinating, the book includes a wealth of self-tests that helps individuals to customize their own decision making based on their unique background and current situation."
Include Bibliography and Index
Keywords: Birth intervals -- Family size--Decision making -- Families